FALLUJAH BATTLES: VIOLATIONS OF THE INTERNATIONAL HUMANITARIAN LAW (UUM Journal of Legal Studies, 2011)
In April and November of 2004, the civilian population of Fallujah City experienced two extremely violent battles (â€œthe Fallujah Battlesâ€) initiated by the Coalition Forces (CF) in Iraq. Marked by the killing and displacement of hundreds of thousands of people in Fallujah City, the Fallujah Battles raise a number of issues related to international humanitarian law (IHL), as well as concerns regarding the legal institutions charged with the protection of international human rights. This article generally discusses the crime allegedly committed against civilians by the CF â€“ which included the USA, UK and Iraqi forces â€“ during the Fallujah Battles. The first part examines the principal IHL instruments considered in relation to acts that were committed during the Battles of Fallujah. The discussion then considers whether actions taken against civilians, civilian properties and medical units by the CF; and the prohibition of International Committee of Red Cross (ICRC) from carrying out its duties in wartime by the CF amount to violations of IHL. The second part considers whether the use of white phosphor constitutes a violation of contemporary IHL, particularly in relation to whether such weapons can be considered chemical weapons prohibited by IHL. Finally, this article discusses the potential legal mechanisms available to prosecute alleged perpetrators of war crimes in Fallujah.Keywords: Fallujah battles, international humanitarian law, Geneva Conventions, war crimes, protection of civilians